2018
DOI: 10.3390/nu10101462
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Evaluation of the eaTracker® Mobile App

Abstract: Background: eaTracker® is Dietitians of Canada’s online nutrition/activity self-monitoring tool accessible via website and mobile app. The purpose of this research was to evaluate the eaTracker® mobile app based on user perspectives. Methods: One-on-one semi-structured interviews were conducted with adult eaTracker® mobile app users who had used the app for ≥ 1 week within the past 90 days. Participants (n = 26; 89% female, 73% 18–50 years) were recruited via email. Interview transcripts were coded using first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…For example, the simplification of data entry allows high accessibility among users, leading to frequent utilization in daily activities. Moreover, apps with higher user satisfaction may result in improved app adherence and long‐term improvement of health behaviors (Lieffers, Arocha et al, ; Lieffers, Valaitis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the simplification of data entry allows high accessibility among users, leading to frequent utilization in daily activities. Moreover, apps with higher user satisfaction may result in improved app adherence and long‐term improvement of health behaviors (Lieffers, Arocha et al, ; Lieffers, Valaitis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Data saturation was decided based on reaching thematic saturation, where we could no longer identify new themes from the interview data [ 30 ]. The semi-structured interview guide ( Supplementary Material 2 ) was developed based on the findings from the quantitative analysis of the application’s usage data and published literature [ 31 , 32 ]. Interview domains included experiences of using the educational lessons, tracking tools, and coaching, and perceptions of its usefulness when managing GDM.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 39 volunteers were recruited, of which 77% were women ( Table 4 ). This was not intentional and we found that women were more motivated to take part, as usual in these kinds of studies (female participants ranged between 60 and 88.5%) ( 4 , 66 69 ).…”
Section: Resultsmentioning
confidence: 97%